5(2x+2)=6-2(x-2)

Simple and best practice solution for 5(2x+2)=6-2(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x+2)=6-2(x-2) equation:



5(2x+2)=6-2(x-2)
We move all terms to the left:
5(2x+2)-(6-2(x-2))=0
We multiply parentheses
10x-(6-2(x-2))+10=0
We calculate terms in parentheses: -(6-2(x-2)), so:
6-2(x-2)
determiningTheFunctionDomain -2(x-2)+6
We multiply parentheses
-2x+4+6
We add all the numbers together, and all the variables
-2x+10
Back to the equation:
-(-2x+10)
We get rid of parentheses
10x+2x-10+10=0
We add all the numbers together, and all the variables
12x=0
x=0/12
x=0

See similar equations:

| 2x+16=31 | | 3b+8=180 | | x2-25x+176=0 | | 4a+1=180 | | b+17=180 | | Y(y-13)=59 | | 20+25x=45+30x | | 20+25x=45+25x | | -123=11p | | -6p-54=0 | | 75d-22=0 | | 21n-45=0 | | 24c+1=0 | | 5y=-31 | | (2/5)^4*(5/2)^-3=(5/2)^2x+5 | | X²-40x-6000=0 | | 20x+262.5-26x=250 | | 20x+26.25(5)=250 | | 6(3–x)–5(2x–4)=4(3x–)+14 | | 9=-4y+6y–5 | | (4-2z)÷3=(3÷4)-(5z÷6) | | 5t–3t+5=0 | | 0.5t–3t+5=0 | | x/11/4x+9=3 | | | | -2q–5=-11 | | 10x+600-60x=250 | | -3+(5y)=7 | | 2x4+1.50=14 | | 5+(7y)=-23 | | 5+(6y)=7 | | 2+(4y)=7 |

Equations solver categories